Biomedical Applications of Lactoferrin on the Ocular Surface - Uxía Regueiro; Maite López-López; Rubén Varela-Fernández; Francisco Javier Otero-Espinar; Isabel Lema (MDPI AG, 2023)
Lactoferrin (LF) is a first-line defense protein with a pleiotropic functional pattern that includes anti-inflammatory, immunomodulatory, antiviral, antibacterial, and antitumoral properties. Remarkably, this iron-binding glycoprotein promotes iron retention, restricting free radical production and avoiding oxidative damage and inflammation. On the ocular surface, LF is released from corneal epithelial cells and lacrimal glands, representing a significant percentage of the total tear fluid proteins. Due to its multifunctionality, the availability of LF may be limited in several ocular disorders. Consequently, to reinforce the action of this highly beneficial glycoprotein on the ocular surface, LF has been proposed for the treatment of different conditions such as dry eye, keratoconus, conjunctivitis, and viral or bacterial ocular infections, among others. In this review, we outline the structure and the biological functions of LF, its relevant role at the ocular surface, its implication in LF-related ocular surface disorders, and its potential for biomedical applications.